Functional Activity Limitation and Quality of Life of Leprosy Cases in an Endemic Area in Northeastern Brazil. - Victor S Santos; Laudice S Oliveira; Fabrícia D N Castro; Vanessa T Gois-Santos; Ligia M D Lemos; Maria do C O Ribeiro; Luis E Cuevas; Ricardo Q Gurgel (Public Library of Science (PLoS), 2015)
BACKGROUND:Few studies have evaluated the association between quality of life (QoL) and functional activity limitations (FAL) of leprosy patients as determined by the Screening of Activity Limitation and Safety Awareness scale (SALSA). AIM:To identify the association between FALs and the QoL of patients during and post leprosy treatment. MATERIALS AND METHODS:Cross-sectional survey of 104 patients with leprosy followed in specialist reference centres in Sergipe, Brazil, between June and October 2014. QoL was evaluated using the World Health Organization-QoL-BREF (WHOQoL-BREF) questionnaire. The SALSA scale was used to measure FALs. RESULTS:Low SALSA scores were present in 76% of patients. QoL scores were lower for the physical and environmental domains, with median (interquartile range (IQR)) scores of 53.6 (32.1-67.9) and 53.1 (46.9-64.8), respectively. There was a statistical association between increasing SALSA scores and lower QoL as measured by the WHOQoL-BREF. CONCLUSION:Functional limitations are associated with lower QoL in leprosy patients, especially in the physical and environmental WHOQoL-BREF domains.